Desain Model Fuzzy Control UAV Berbasis Matlab/Simulink pada Arduino Flight Controller - Muchamad Malik; Aan Burhanuddin (Jurnal Engine: Energi, Manufaktur, dan Material, 2018)
Quadrocopter is an aerial vehicle platform that has become very popular among researchers from the past because it has advantages compared to conventional helicopters. The quadrocopter design is very simple and unique but seen from an unstable aerodynamic standpoint. From existing research, researchers have proposed many control system designs for quadrocopter. In this study, the author presents a fuzzy logic controller for quadrocopter. The method in this research is by designing hardware. After that the design for fuzzy controllers. Then the designed fuzzy controller is tested in the Hardware In Loop (HIL) setting. The experimental results and validation of the controller application functions are considered satisfactory and it is concluded that it is possible to stabilize quadrocopter with fuzzy logic controller.